The timing of environmental policy in a duopolistic market - Rafael Moner-Colonques; Santiago Rubio (Economía Agraria y Recursos Naturales)
In this paper the strategic use of innovation by two polluting firms to influence environmental policy is evaluated. The analysis is carried out by comparing two alternative policy regimes for two policy instruments: Taxes and standards. The first of the regimes assumes that the regulator commits to an ex-ante level of the policy instrument. In the second one, there is no commitment. The results show that when there is no commitment and a tax is used to control emissions, the strategic behavior of firms can be welfare improving if the efficiency of the clean technology is relatively low. If this is not the case, the strategic behavior of the duopolists has a detrimental effect on welfare regardless of the policy instrument used to control emissions.